Analisis Personalitas dan Kebijakan Sumber Daya Manusia Terhadap Kinerja Layanan pada Industri Restoran Waralaba di Kota Manado - Laoh, Saartje Dompas (JBE (Journal of Business and Economics); Volume 11 No.1, 2012 JBE UNKLAB, 2012)
The purpose of this research is to investigate the impact of the personality factors and human resource policy contributes to employee service performance .   The research population  is the restaurant chains within the city of Manado, North Celebes.  This research uses  purposive sampling method which distributes questionnaire to 60 employees and 150 customers.  Then the data gathered are analyzed using analysis regression technique.  The result of this analysis are evident  in these findings .  First, empirically, personality is proven to have a positive relationship and have a significant contribution toward the employee service perfomance.  Second, there exists a relationship and significant correlation between human resource policies and employee level of service.  Third, personality and human resource policy when tested together is proven to have a significant influence toward employee service performance.